Progressive stridor after carotid endarterectomy: Case report and literature review - E Lavrysen; HTC Veger; JJ Wever; H Blom (Annals of Vascular Surgery - Brief Reports and Innovations, 2022)
Introduction: Cranial nerve injury (CNI) is a common complication of carotid endarterectomy (CEA), with an incidence varying between 3% and 30% according to the definition of CNI and diagnostic modalities. The recurrent laryngeal branch of the vagus nerve (CN X) is the third most commonly injured nerve during CEA. The vast majority of CNI (99.3%) are due to neuropraxia and therefore transient. Report: A 72-year-old male with a history of multiple ischemic cerebrovascular attacks (CVA) received an elective carotid endarterectomy on the left side. The postoperative period was complicated with acute inspiratory stridor. Evaluation by the Ear, Nose, Throat (ENT) department showed bilateral vocal cord palsy due to neuropraxia during the endarterectomy with pre-existent paralysis of the right vocal cord caused by the previous CVA. Since the patient had been aphasic for several years, hoarseness due to unilateral vocal cord palsy could not be assessed preoperatively. Discussion: Acute stridor is caused by a sudden narrowing of the airway due to the median position of both paralysed vocal cords. Patients often require a tracheotomy to secure the airway. Most cases of bilateral vocal cord dysfunction are provoked by the inability to recognize pre-existent unilateral recurrent laryngeal nerve (RLN) paralysis. Thorough screening and adequate history taking are paramount to prevent this rare condition. Symptoms of unilateral injury to the RLN include hoarseness, dysphonia, cough, dysphagia or aspiration. However, patients may be entirely asymptomatic in up to 32% of unilateral RLN lesion cases, leading to decreased sensitivity of exclusively screening with physical examination. Laryngeal examination to assess vocal cord function is recommended for patients who are either hoarse, have a history of laryngeal trauma, are known with neurological deficits or have undergone previous surgical procedures associated with a high risk of unilateral vocal cord paralysis, even if they are presently asymptomatic.